2015
DOI: 10.1007/s00455-015-9618-1
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Radiation Dose on Swallowing: Evaluation of Aspiration and Kinematics

Abstract: Radiation oncologists have focused on the pharyngeal constrictors as the primary muscles of concern for dysphagia. However, our prior investigations have demonstrated that radiation dose to the geniohyoid rather than the constrictor muscles was more closely related to penetration aspiration scores (PAS). We examined the relationship between (1) radiation dose and swallowing temporal kinematics, and (2) between PAS and swallowing kinematics in these patients. Videofluoroscopic swallowing studies of 41 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
32
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(35 citation statements)
references
References 25 publications
2
32
1
Order By: Relevance
“…Pharyngeal constrictors and the larynx were first identified by multiple investigators as primary dysphagia-aspiration-related organs (DARS) [95]. Beyond the classic DARS, emerging work suggests relevance of dose/volume distributions to submental musculature (i.e., geniohyoid, mylohyoid) that are critical to elevate the hyolaryngeal complex and assist with cervical esophageal opening [96,97]. Reporting normal tissue complications probabilities as a function of DARS, Eisbruch et al gave solid ground for efforts to reduce dysphagia in the IMRT era [95,98,99].…”
Section: Dysphagiamentioning
confidence: 99%
“…Pharyngeal constrictors and the larynx were first identified by multiple investigators as primary dysphagia-aspiration-related organs (DARS) [95]. Beyond the classic DARS, emerging work suggests relevance of dose/volume distributions to submental musculature (i.e., geniohyoid, mylohyoid) that are critical to elevate the hyolaryngeal complex and assist with cervical esophageal opening [96,97]. Reporting normal tissue complications probabilities as a function of DARS, Eisbruch et al gave solid ground for efforts to reduce dysphagia in the IMRT era [95,98,99].…”
Section: Dysphagiamentioning
confidence: 99%
“…As such, external radiation may be partially absorbed by soft tissue within the submandibular space (i.e., submandibular glands and lymph nodes), lessening the radiation dose to the suprahyoid muscles. Two dosimetry studies were recently conducted correlating dysphagia with radiation dose to the genioglossus and submental complex [52,50]. Kumar et al [52] measured dosimetric characteristics in genioglossus, and found that a minimum dose (30 Gy) strongly correlated with abnormal (≥3) penetration-aspiration scores.…”
Section: Temporal Differences In Radiation Injurymentioning
confidence: 99%
“…Starmer et al (2015) reported that patients with post-radiated submental muscles who penetrated and aspirated also had decreased dLVC (Starmer et al, 2015). These, and many other studies that link disordered LVC to aspiration, highlight the complexity of LVC mechanics and its pathophysiology (Lee et al, 2016; Power et al, 2009; Power et al, 2007).…”
Section: Discussionmentioning
confidence: 99%